Effects of wastewater parameters on the growth and behavioral characteristics of microalgae - Alagesan, Alpravinta (2025)
This study investigates a cost efficient technique of microalgae cultivation via the utilization of wastewater as a cheaper, alternative culture media. Effects of significant intrinsic wastewater parameters; nitrogen, chemical oxygen demand, phosphorus and pH, that are crucial to microalgae growth, were studied via the design of experiments to better understand their role in the growth process. Findings revealed that nitrogen and chemical oxygen demand were highly influential, with optimized conditions under high concentrations resulting in maximum biomass productivity. Further analysis highlights the importance of maintaining a good nutrient balance in the culture media, and the potential impact of these parameters, particularly at extreme concentrations, on the microalgal metabolic pathway and cellular activity regulation. The biomass yield obtained at optimized culture conditions was about four times higher than in raw culture conditions while, its protein content increased by about 12 % showing the significance of the optimization carried out.